Penanganan Fisioterapi pada Kasus Bell Palsy Dextra menggunakan intervensi TENS, Massage dan Mirror Exercise : a Case Report - Alviana Dwi Lestari; Umi Budi Rahayu; Mulyanto Mulyanto (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Background: Bell's Palsy is a condition of facial muscle weakness due to inflammation or damage to the VII cranial nerve (facial nerve), which is classified as a primary acute idiopathic lower motor neuron (LMN) type. This condition is characterized by unilateral facial paralysis and pain in the mastoid area, which can affect the patient's quality of life. Method: This study design used a case report method which observed one patient with a case of Bell Palsy Right. Physiotherapy intervention was carried out during four meetings at Dr. Moewardi Hospital, with therapy modalities including Transcutaneous Electrical Nerve Stimulation (TENS), massage, and mirror exercise. Evaluation was carried out using the Numeric Rating Scale (NRS) for pain, Manual Muscle Testing (MMT) for facial muscle strength, and the Ugo Fisch scale for functional ability. Results: This study shows that physiotherapy treatment during 4 meetings resulted in decreased pain, increased muscle strength, and increased functional ability with Bell palsy. Conclusion: Physiotherapy interventions in the form of TENS, massage, and mirror exercise are effective in reducing pain, increasing muscle strength, and improving functional abilities in patients with Bell's Palsy Right.